Fluoroscopy-Assisted Thoracoscopic Resection for Small Intrapulmonary Lesions after Preoperative Computed Tomography-Guided Localization Using Fragmented Platinum Microcoils - Moon, Seok Whan; Cho, Deog Gon; Do Cho, Kyu; Kang, Chul Ung; Seop Jo, Min; Park, Hyun Jin (The Thoracic and Cardiovascular Surgeon, 2012)
Background Preoperative localization is frequently necessary to perform thoracoscopic resection of a small and/or deeply located intrapulmonary lesion. We developed a new method that uses a fragmented platinum microcoil, and retrospectively evaluated the efficacy of our technique.Methods Between January 2006 and May 2010, self-made microcoils (Easimarker) were used to localize total 32 lesions (21 solid nodules, and 11 ground glass opacities) in 30 patients. Computed tomography-guided localization was performed into, or just around the lesions. Localized lesions were resected using fluoroscopy-assisted thoracoscopic surgery (FATS), and the histopathologic diagnosis was confirmed. The accuracy and complications of the localization procedure, and operative results of FATS were observed.Results Mean size and depth of all lesions were 11.8 ± 5.1 mm (range: 3 to 22) and 12.2 ± 7.1 mm (range: 2 to 30). CT-guided localizations were successfully performed in all lesions. Four minimal pneumothorax and one parenchymal hematoma related with localization procedure occurred. There were three repeated procedures, which resulted from pleural rebounding of the microcoils. There were two microcoil detecting failures due to intrathoracic displacement during FATS. All 32 resected lesions were histopathologically diagnosed.Conclusion CT-guided localization using the fragmented microcoil combined with FATS of small intrapulmonary lesions is a safe, effective, and a diagnostically accurate procedure.
Keywords: pulmonary nodule; microcoil; thoracoscopy/VATS; preoperative localization